KELUARNYA INGGRIS DARI UNI EROPA DITINJAU DARI HUKUM ORGANISASI INTERNASIONAL (STUDI KASUS: REFENDUM BREXIT) - Karina Stefanie (Gloria Justitia, 2022)
The European Union is the largest multilateral organization in the world consisting of sovereign and independent countries consisting of 28 countries. However, in 2019, the number of registered member countries was 27 member countries due to the Brexit Referendum, Britain's withdrawal from the European Union membership which was held on June 23, 2016. This paper analyzes the relationship between the UK and the European Union, and the causes of the Brexit Referendum then reviewed from the Law of International Organizations. The research method used is normative-empirical legal research with secondary source data from books, journals, internet sites, laws and regulations and applicable international agreements. The results and discussion of this paper are the cause of Britain's exit from the EU membership due to EU policies that are considered detrimental to the UK and too deep intervention and integration by the European Union, so UK's exit process was carried out in accordance with Article 50 of the Treaty of Lisbon where in 2017 the UK submitted a letter of resignation to the European Union. And after several joint negotiations, the UK finally officially left the European Union on March 29, 2019. So, the whole process until UK officially left the European Union, was in accordance with the procedures in Article 15 and Article 50 of the Treaty of Lisbon.